Kajian Manfaat Taman Bagi Kesehatan Mental Masyarakat di Kota Sukabumi Selama Pandemi COVID-19 - Dewi, Kania Puspita; Sulistyantara, Bambang; Pratiwi, Prita Indah (Jurnal Lanskap Indonesia, 2024)
The COVID-19 pandemic has increased mental health problems in Sukabumi City. Urban parks can integrate environment, society, and health in urban environments by promoting an ecological approach based on contact with nature. This study aims to analyze the effect of performing activities for at least 20 minutes in Taman Alun-alun and Taman Lapang Merdeka on mental health visitors with a sample of 30 people in each park selected through purposive sampling. The data collection method used was experimental, with the One Group Pretest-Posttest research design through The Mental Health Inventory (MHI-38) questionnaire, which had been tested for validity and reliability. The data analysis method used is the Paired Samples T-test with SPSS 22. The results show that performing activities in a city park for at least 20 minutes can improve the mental health of visitors aged 18-25 years during the COVID-19 pandemic, with the highest increase in the average mental health score in Taman Lapang Merdeka because it provides facilities for physical and non-physical activities.